The optimization of technical trading strategy using genetic algorithm approach / Khairunnisa Musa - Musa, Khairunnisa (2006)
Recently, the use of genetic algorithm for the optimization of technical trading strategies has been receiving a great deal of attention. A technical trading strategy involves the study of past behavior in order to draw conclusions concerning the direction and magnitude of future price movement. Technical models are designed to keep investor trading with the trend. Understanding the best trend could produce a promising lucrative investment. This research is about an application of technical trading strategy to foreign exchange market by using Standard Genetic Algorithm (STDGA). Genetic algorithm is used as a tool to efficiently search for the most attractive solution as a suggestion for the trader to trade in foreign currencies. Results from the function optimization shows that STDGA is effective and efficient in locating the optimal solution (the maximum value of the Sharpe Ratio). COPYRIGHT ©